2017
DOI: 10.1097/meg.0000000000000778
|View full text |Cite
|
Sign up to set email alerts
|

Serum alanine aminotransferase levels and all-cause mortality

Abstract: Increase in serum ALT within the normal range is initially associated with lower mortality, but has no effect after 17 U/l. The elderly show a significantly larger decrease in mortality with an increase in ALT than younger individuals. The mechanisms underlying this relationship need further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
5
12
0
Order By: Relevance
“…As also shown in previous studies [1][2][3][4][5][6]9,11,12], we found that people with low serum ALT activity are at a higher risk of mortality. However, the ranges of serum ALT activity that made positive and negative contributions to mortality overlapped (Figure 1 and Figure 3), which may have reduced the overall contribution calculated for serum ALT activity in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As also shown in previous studies [1][2][3][4][5][6]9,11,12], we found that people with low serum ALT activity are at a higher risk of mortality. However, the ranges of serum ALT activity that made positive and negative contributions to mortality overlapped (Figure 1 and Figure 3), which may have reduced the overall contribution calculated for serum ALT activity in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…It can be difficult to identify older members of the community who are at a high risk of mortality, particularly using the conventional biochemical parameters measured in clinical practice. During the past two decades, many studies have shown that low serum alanine aminotransferase (ALT) activity and high aspartate transaminase (AST)/ALT ratio are associated with high mortality in older people [1][2][3][4][5][6][7][8][9][10][11][12][13]. However, the mechanisms involved remain to be conclusively established [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, patients in the lowest quartile of ALT randomized to placebo had minimal to unchanged mean ALT values that remained ≤ 15 U/L through 48 weeks of treatment. In the general population, serum concentrations of ALT < 17 U/L are associated with increased all‐cause mortality 47,48 . Therefore, increases in ALT induced by bardoxolone methyl, particularly in the subset of patients with the lowest serum ALT concentrations, may reflect restoration of Nrf2 and ALT activity to normal levels and are therefore associated with the improved metabolic and anti‐inflammatory effects of bardoxolone methyl treatment.…”
Section: Discussionmentioning
confidence: 99%
“…GOT, also known as aspartate aminotransferase, is a mitochondrial and cytoplasmic enzyme, with an important role in cell energy production [ 56 ]. Alterations in GOT levels in blood are considered well-known markers of hepatic, myocardial and skeletal muscle cytolysis, while GPT also known as alanine aminotransferase, is mainly a hepatic cytoplasmic enzyme [ 57 , 58 , 59 ]. In our study, the lack of a significant association between PEF and GPT levels in blood suggests that the association between PEF and GOT levels is related to myocardial or skeletal muscle metabolism.…”
Section: Discussionmentioning
confidence: 99%